Dyslipidemia and Cardiovascular Disease Prevention in South Asians: A Review and Discussion of Causes, Challenges and Management Strategies - Saeed, Anum; Virani, Salim S.; Mulukutla, Suresh; Chow, Clara K. (Current Diabetes Reviews, 2021)
Background: South Asians are at a significantly increased risk of atherosclerotic cardiovascular disease (ASCVD). For a major portion of the South Asian population, the cardiovascular disease events occur at a relatively younger age, are associated with worse outcomes, and have potentially more severe socioeconomic implications compared to their western counterparts. Methods: The term “South Asian” typically constitutes individuals from India, Pakistan, Nepal, Bhutan, Bangladesh, Sri Lanka, and Maldives, including expatriates as well as their families from these countries. Based on this, South Asians form approximately 25% of the world’s population, with a high ASCVD burden in this group. In this review, we discuss the pathophysiological factors underlying ASCVD in South Asians, the dyslipidemia types and management, and discuss approaches to improve the overall ASCVD prevention efforts in this large subset population of the world. Although the pathophysiological mechanisms underlying the excess risk of cardiovascular disease in South Asians are multifactorial, dyslipidemia is a primary risk factor for the incidence and prevalence of this disease. The traditional “South Asian” dyslipidemia pattern includes levels of low-density lipoprotein cholesterol (LDL-C) in the normal range with a high concentration of LDL particles, elevated triglycerides, low levels of high-density lipoprotein cholesterol (HDL-C) with dysfunctional HDL particles, and high levels of lipoprotein(a). Conclusion: While combined efforts to study the expatriate South Asians in western countries have been able to identify South Asian specific dyslipidemias, causal associations and optimal management remain relatively less explored. Larger scale studies are needed to better quantify the relationship of each lipid parameter with ASCVD risk among South Asians as well as optimal lipid targets and management strategies to reduce morbidity and mortality in this high-risk group.
Keywords: atherosclerotic cardiovascular disease (ASCVD)